2022
DOI: 10.3390/catal12040363
|View full text |Cite
|
Sign up to set email alerts
|

Prospects and Technical Challenges in Hydrogen Production through Dry Reforming of Methane

Abstract: Environmental issues related to greenhouse gases (GHG) emissions have pushed the development of new technologies that will allow the economic production of low-carbon energy vectors, such as hydrogen (H2), methane (CH4) and liquid fuels. Dry reforming of methane (DRM) has gained increased attention since it uses CH4 and carbon dioxide (CO2), which are two main greenhouse gases (GHG), as feedstock for the production of syngas, which is a mixture of H2 and carbon monoxide (CO) and can be used as a building block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 163 publications
0
8
0
Order By: Relevance
“…Compared to SMR and POX, dry reforming of methane (DRM, eq ) presents a viable pathway capable of achieving low-carbon H 2 initiatives . DRM can utilize CO 2 and CH 4 from a diverse slate of feedstocks like shale gas, biogas, and landfill gas to form syngas.…”
Section: Plasma Catalysis For Hydrogen Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to SMR and POX, dry reforming of methane (DRM, eq ) presents a viable pathway capable of achieving low-carbon H 2 initiatives . DRM can utilize CO 2 and CH 4 from a diverse slate of feedstocks like shale gas, biogas, and landfill gas to form syngas.…”
Section: Plasma Catalysis For Hydrogen Generationmentioning
confidence: 99%
“…Consequently, high feed flow rates are necessary to maintain the arc evolution and discharge stability during the GA discharge. However, the primary challenges in conventional GA reactors involve addressing the low gas conversions caused by the short residence time of the reactants and electrode deterioration due to the carbon deposition on the electrode surface. , Various studies have reported rotating gliding arcs (RGAs) to address these issues.…”
Section: Overview Of Plasmas and Plasma (Discharge) Types For Hydroge...mentioning
confidence: 99%
“…Dry reforming of methane (DRM) is highly attractive because it converts methane (CH 4 ) and carbon dioxide (CO 2 ), two of the most important greenhouse gases, into syngas (H 2 + CO), which can be used as the feedstock for the synthesis of value-added chemicals, for example, long-chain hydrocarbon. DRM is a strong endothermic reaction, which needs to be carried out at high temperatures (typically between 550 and 1000 °C). Side reactions, such as methane cracking and CO disproportion, are considered the main pathways for carbon formation. , Thus, the catalysts used for DRM should be thermostable and anticoking.…”
Section: Introductionmentioning
confidence: 99%
“…4−6 Side reactions, such as methane cracking and CO disproportion, are considered the main pathways for carbon formation. 5,6 Thus, the catalysts used for DRM should be thermostable and anticoking.…”
Section: Introductionmentioning
confidence: 99%
“…The dry reforming of methane (DRM) plays an important role in sustainability because it can convert two major greenhouse gases through one single reaction, CH 4 + CO 2 → 2CO + 2H 2 [1][2][3]. The mixture of hydrogen and carbon monoxide produced through this reaction can be further transformed into fuels and chemicals through the Fischer-Tropsch reaction [4,5].…”
Section: Introductionmentioning
confidence: 99%